Changing Incidence of Inflammatory Bowel Disease: Environmental Influences and Lessons Learnt from the South Asian Population - Foster, Alice; Jacobson, Kevan (Frontiers in Pediatrics, 2013)
Inflammatory bowel disease (IBD) is a chronic relapsing inflammatory disorder of the gastrointestinal tract associated with significant morbidity. While IBD occurs in genetically susceptible individuals, the etiology is multifactorial, involving environmental influences, intestinal dysbiosis and altered immune responses. The rising incidence of IBD in industrialized countries and the emergence of IBD in countries with traditionally low prevalence underscore the importance of environmental influences in the pathobiology of the disease. Moreover the high incidence of IBD observed in the South Asian immigrant population in the United Kingdom and Canada further supports the influence of environmental factors.